DHOW2 score leads to significant improvement in acute stroke care management emergency department: a prospective analysis. Issue 4 (3rd December 2019) - Akhtar, Naveed; Salam, Abdul; Bourke, Paula; Kamran, Saadat; Bhutta, Zain; Joseph, Sujatha; Santos, Mark; Morgan, Deborah; Thomas, Stephen; Ajwad Butt, Adeel; Shuaib, Ashfaq
Abstract : Background: Delays in transfer of patients from emergency department (ED) to stroke ward increases medical complications. We evaluate if a new risk-score 'DHOW2' (dysphagia, hemiplegia, observation-required, wet (incontinence) and weight) will identify high-risk patients and whether expedited admission of 'high-DHOW2' score patients to SW will result in fewer complications. Methods: The DHOW2 score was designed to determine risk of complications following acute stroke. Phase I (279 patients) tested rates of complications with increasing DHOW2. Phase II (1091 patients), evaluated if early admission to the SW of high-DHOW2 patients will lead to fewer complications. Phase III (1257 patients) monitored implementation of the DHOW2 following completion of the study. Findings: Medical complications increased with higher-DHOW2 scores during all three phases; 0%–0.8% with DHOW2 of ≤3, 3.1%–6.5% with DHOW2 of 4–5 and 10.9%–14.1% with DHOW2 of ≥6 (p=<0.001). In phase II, more high-DHOW2 patients were admitted expeditiously to the SW from ED resulting in fewer complications, and fewer deaths. The odds of medical complications with DHOW2 of ≥6 was 36.8–58.3 compared with DHOW2 of ≤3. Expedited SW admission of 'high-DHOW2 patients' to within 8 hours reduced the development of complications to odds of 19.18–30.17 (p<0.001). Interpretations: The DHOW2 score detects patients at risk of AS related medical complications. It is easy to implement in busy EDs where nurses can use the score to identify such patients. The risk stratification by DHOW2 and early transfer of high-scoring patients to SW is associated with significantly fewer complications.